Volume 1: Offshore Technology 2013
DOI: 10.1115/omae2013-11332
|View full text |Cite
|
Sign up to set email alerts
|

Bend Over Sheave Durability of Fibre Ropes for Deep Sea Handling Operations

Abstract: This paper describes work performed within a Joint Industry Project aiming to evaluate the lifetime of deep sea handling ropes. Various HMPE (High Modulus Polyethylene) fiber ropes, with and without coatings, have been studied under both tensile and cyclic bend over sheave (CBOS) loading. A large test program has enabled both tension-cycle to failure relationships and empirical expressions for residual strength after cycling to be determined. A special device was then developed to apply a known couple to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…These do not give the same result for a new rope, and preliminary tests showed that the latter result in lower break loads, both for new ropes and after cyclic loading, Fig. 5 (Davies et al, 2013). A direct tension value of residual strength (although a practical in-service retirement criteria) may therefore provide an over-optimistic evaluation of remaining properties in a deep sea handling application.…”
Section: Residual Strength After Cyclingmentioning
confidence: 74%
See 3 more Smart Citations
“…These do not give the same result for a new rope, and preliminary tests showed that the latter result in lower break loads, both for new ropes and after cyclic loading, Fig. 5 (Davies et al, 2013). A direct tension value of residual strength (although a practical in-service retirement criteria) may therefore provide an over-optimistic evaluation of remaining properties in a deep sea handling application.…”
Section: Residual Strength After Cyclingmentioning
confidence: 74%
“…It should be emphasized that this is a standard rope design. There are several enhanced bending designs available commercially, some of which were also tested in the project (see Davies et al, 2013), and the approach developed here can be applied to other designs. The specimens tested were around 8 m long, with eye splices at both ends.…”
Section: Materials and Test Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach has been developed by Durville (2010), based on finite element modeling with special algorithms to account for the interactions between elements. This has been used to simulate the tension, torsion, and bend over sheave response of braided fiber ropes (Vu et al, 2015;Davies et al, 2013Davies et al, , 2016.…”
Section: Aging Of Ropes In Servicementioning
confidence: 99%